Composição ministerial e tamanho de governo no Brasil: uma análise do período de 1985 a 2019, sob a ótica da escolha pública. - Ghizellini, Mariangela (2021)
From the concern with the extension of the State's power over the direction of the economy, and consequently under the direction of the lives of individuals in a society, this work intends to analyze, from the perspective of the theory of public choice, how the ministerial composition affects public spending and the size of government, taking into account governance in the Brazilian multiparty presidential system. Federal public spending from 1985 to 2019 will be analyzed, based on party fragmentation and ministerial composition through federal government expenditure data for the same period, from the Union's budget execution expenditure lines, which will be combined with the data referring to the ministerial composition in the same period, with the intention of observing the party fragmentation in the composition of the government coalition. The correlation of these variables will be able to signal whether a greater party fragmentation in the government coalition and a greater number of spending order ministries are or are not linked to a larger government size.